Understanding Bereavement among College Students: Implications for Practice and Research - Bistricean, Cristina; Shea, Munyi (International Dialogues on Education Journal, 2021)
The experience of losing a first-degree family member, followed by a second-degree family, and a close friend is prevalent among college students. Bereavement affects student success as they must balance grief and academics. Culture also influences the expression and experience of grief, making it essential to understand grief and bereavement in context. The recent COVID-19 global pandemic has exacerbated the experience of loss and grief among college students, which warrants a better understanding and intervention for disenfranchised grief. Social and emotional support for disenfranchised grief is not always provided, as this type of grief is often socially unsanctioned. The lack of support and understanding could make it difficult for individuals with disenfranchised grief to cope with the demands of higher education and bereavement process. Counseling implications for how universities and colleges could intervene on the bereaved student's behalf are discussed.